Multiple ACL Revision: Failure Analysis and Clinical Outcomes - Dini, Francesco; Tecame, Andrea; Ampollini, Aldo; Adravanti, Paolo (The Journal of Knee Surgery, 2019)
Anterior cruciate ligament (ACL) reconstruction represents one of the most successful orthopedic surgical procedures. Nevertheless, ACL revisions are still very frequent, with a small but relevant number of failures. The purpose of this study is to analyze the failure causes and the clinical outcomes of patients who underwent a re-revision ACL reconstruction. Between January 2009 and December 2017, 263 ACL revisions were performed by a single senior surgeon. Seventeen patients (12 males and 5 females) underwent re-revision ACL reconstruction meeting the inclusion criteria. The mean age was 28.4 years (range, 19–41 years). Before the re-revision, the patients were evaluated preoperatively and after a mean follow-up of 29 months (range, 13–58 months). Assessment included subjective and objective evaluations (Lysholm and International Knee Documentation Committee [IKDC]), KT-2000 arthrometer, radiographic study, and preoperative computed tomography scan. Five patients showed a too anterior previous femoral tunnel and seven a too vertical and posterior tibial tunnel; eight meniscal tears were found. Five patients had grade III–IV according to Outerbridge cartilage lesions. IKDC showed a statistically significant improvement (A + B 35%, C + D 65% preop, A + B 82%, C + D 18% postop, odds ratio: 0.1169; p = 0.0083). The mean Lysholm score ranged from 43 ± 9 to 87 ± 7 (p < 0.001). The KT-2000 arthrometer showed a statistically significant improvement from a mean of 5.8 ± 1.4 to 1.5 ± 1.1 (p < 0.001) at last follow-up. Out of 17 patients, only 4 returned to sports activity at the same preinjury levels. Postoperatively at the last follow-up after last revision surgery, no osteoarthritis evolution was observed. This study showed good clinical and radiological results after the last revision ACL surgery in patients with multiple failures of ACL reconstruction but only one-fourth of the patients returned to the same preoperative sport level. Traumatic events, technical errors, and untreated peripheral lesions are the main causes of multiple previous failures; the worst clinical outcomes were found in the patients with high grade of chondral lesions.
Keywords: ACL; ACL revision; failure ACL reconstruction; return to sport